2015
DOI: 10.1088/0004-6256/149/5/161
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Extinction in the Direction of the Open Cluster M29

Abstract: The interstellar extinction is investigated in a 1.5 deg 2 area in the direction of the open cluster M29 (NGC 6913) in Cygnus, centered at R.A. = 20 h 24 m , decl. = +38°30′. The study is based on photometric classification of 1110 stars in spectral and luminosity classes down to V = 19 mag using photometry in the Vilnius seven-color system published in Paper I (Milašius et al. 2013). Additionally, in the same area the extinction is investigated using 1147 red clump giants (RCGs), identified by combining selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…Most probably, this jump in extinction is related to the cloud system of the Great Cygnus Rift. A similar jump has been found in our earlier papers (Straižys et al 2014(Straižys et al , 2015 in the direction of the nearby cluster M29. The next increase in extinction is observed at d > 1.7 kpc.…”
Section: Interstellar Extinction In the Cluster Areasupporting
confidence: 90%
“…Most probably, this jump in extinction is related to the cloud system of the Great Cygnus Rift. A similar jump has been found in our earlier papers (Straižys et al 2014(Straižys et al , 2015 in the direction of the nearby cluster M29. The next increase in extinction is observed at d > 1.7 kpc.…”
Section: Interstellar Extinction In the Cluster Areasupporting
confidence: 90%
“…It must be borne in mind that the distances to the Cygnus OB1 association clusters appear to show greater uncertainty than other clusters located in other Galactic regions for which the photometric parallax is more precise. The distribution of dust in the region could be the cause of this imprecision in the distance, as Straizys et al (2015) have recently concluded with their reanalysis of the cluster NGC 6913 (M29).…”
Section: Clustering In the Phase Space: Opticsmentioning
confidence: 91%
“…Red supergiants at distances comparable to those of the OB associations are expected to appear very bright at near-infrared wavelengths, and also have very red colors due both to their low photospheric temperatures and to the foreground extinction, mainly associated with the Cygnus Rift (Straižys et al 2015). We made an initial selection of all the stars in the 2MASS Point Source Catalog in the area defined above having K S < 4.0, J − K S > 1.1.…”
Section: Red Supergiants In Cygnusmentioning
confidence: 99%